2007
DOI: 10.1124/jpet.106.119073
|View full text |Cite
|
Sign up to set email alerts
|

Differential Inhibition of Rat and Human Na+-Dependent Taurocholate Cotransporting Polypeptide (NTCP/SLC10A1)by Bosentan: A Mechanism for Species Differences in Hepatotoxicity

Abstract: Bile acid accumulation in hepatocytes due to inhibition of the canalicular bile salt export pump (BSEP/ABCB11) has been proposed as a mechanism for bosentan-induced hepatotoxicity. The observation that bosentan does not induce hepatotoxicity in rats, although bosentan has been reported to inhibit rat Bsep and cause elevated serum bile acids, challenges this mechanism. The lack of hepatotoxicity could be explained if bosentan inhibited hepatocyte uptake as well as canalicular efflux of bile acids. In the curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
93
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 123 publications
(103 citation statements)
references
References 39 publications
(54 reference statements)
10
93
0
Order By: Relevance
“…Bosentan and troglitazone demonstrated similar effects on the hepatobiliary disposition of d 8 dmd.aspetjournals.org inhibition of the efflux of d 8 -TCA into bile. These results are consistent with the findings of Leslie et al (2007) in which bosentan was identified as a potent inhibitor of rat Ntcp. Furthermore, Kemp et al (2005) also observed inhibition of hepatic uptake and biliary efflux of TCA by troglitazone coadministration in SCRH.…”
Section: Discussionsupporting
confidence: 82%
“…Bosentan and troglitazone demonstrated similar effects on the hepatobiliary disposition of d 8 dmd.aspetjournals.org inhibition of the efflux of d 8 -TCA into bile. These results are consistent with the findings of Leslie et al (2007) in which bosentan was identified as a potent inhibitor of rat Ntcp. Furthermore, Kemp et al (2005) also observed inhibition of hepatic uptake and biliary efflux of TCA by troglitazone coadministration in SCRH.…”
Section: Discussionsupporting
confidence: 82%
“…Covalent adduct formation, immunotoxicity, and disruption of cellular bioenergetics have been considered previously as mechanisms underlying hepatotoxicity, but more recent data suggest that hepatic transport proteins may be an important site of toxic interactions (Fattinger et al, 2001;Funk et al, 2001;Leslie et al, 2007). The objective of this study was to evaluate the capability of sandwich-cultured primary rat hepatocytes (SCRH), which more closely mimic the metabolic and transport capabilities of the intact liver, to predict the hepato-protective effect of DEX against trabectedin-mediated hepatotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…The Na + -dependent taurocholate cotransporting polypeptide (NTCP, SLC10A1), which is a major transporter of bile acids in hepatocytes, showed species differences in terms of its inhibition by bosentan. 26) Taurocholate uptake was inhibited in a competitive manner by bosentan in the human NTCP with a K i value of 18 µM, whereas the uptake of taurocholate was inhibited in a noncompetitive manner by bosentan in the rat NTCP. Multidrug resistance-associated protein 2 (MRP2, ABCC2) transports a variety of different drug molecules and metabolites, including glutathione, glucuronide, and sulfate conjugates, across extraand intracellular membranes.…”
Section: Discussionmentioning
confidence: 99%